A Novel Role of Candesartan and Ramipril in Attenuation of Liver Fibrosis in Patients with Chronic Hepatitis C Viral Infection - Tarek M. Mostafa; Gamal A. El-azab; Gamal A. Badra; Alyaa S. Abdelwahed; Abeer A. Elsayed (New Horizons in Medicine and Medical Research Vol. 11, 2022)
The purpose of this study was to evaluate the effects of Candesartan and Ramipril on liver fibrosis in patients with chronic hepatitis C. A total of 64 individuals with chronic hepatitis C and liver fibrosis participated in this randomized controlled prospective research. Participants were randomized into three groups; group I (control group; n=21) which received traditional therapy only, group 2 (Ramipril group; n=21) which received traditional therapy plus 1.25 mg/day oral Ramipril and group 3 (Candesartan group; n=22) which received traditional therapy plus 8 mg/day oral Candesartan. The three study groups had statistically identical demographic and laboratory data at the start. After treatment, the three study groups showed significant decrease in liver stiffness, serum levels HA and TGF-\(β\)1, and indices of liver fibrosis as compared to baseline data (p<0.001). Patients on Ramipril and Candesartan exhibited significant improvement in all evaluated parameters six months following treatment when compared to the control group. In addition, when compared to Ramipril, the Candesartan group demonstrated a significant reduction in liver stiffness, biomarkers, and fibrosis indices. Ramipril and Candesartan were well tolerated and effective in treating liver fibrosis in chronic hepatitis C patients with hepatic fibrosis. Candesartan, an AT1-R antagonist, sustained anti-fibrotic activity better than Ramipril, suggesting that it could be a safe and effective treatment for liver fibrosis in individuals with chronic liver disease.